Crystallization kinetics of Al2O3-26mol%Y2O3 glass and full crystallized transparent Y3Al5O12-based nanoceramic. Issue 2 (February 2021) - Zhang, Ying; Ma, Xiaoguang; Li, Xiaoyu; Yang, Lixia; Ge, Binghui; Allix, Mathieu; Li, Jianqiang
Abstract: Transparent Y3 Al5 O12 -based polycrystalline ceramics with excessive Al2 O3 composition (Al2 O3 -26 mol%Y2 O3, AY26) have been demonstrated as potential host materials for phosphor applications. However, the crystallization mechanism of AY26 glass has not been thoroughly investigated so far. In this work, the non-isothermal crystallization kinetics of AY26 glass was experimentally analyzed. The AY26 glass depicts high activation energy and crystallization mechanism of volume nucleation followed by three-dimensional crystal growth mode. Based on the analysis, a novel highly transparent YAG-Al2 O3 nanoceramic material was elaborated at lower temperature of 963 ℃ by using pressureless glass crystallization. The biphase nanoceramic is characterized by the structure of YAG nanocrystals surrounded with homogeneous thin Al2 O3 layers. It is extremely transparent from visible to mid-infrared region, particularly the transmittance can reach the theoretical limit of YAG transparent ceramic in NIR and MIR regions. Besides, it has almost same hardness of 21 GPa with YAG single crystal and YAG transparent ceramic.